Cognitive vulnerabilities to anxiety : a bridge between personality and symptoms - Sučević, Mirjana (Array, 2019)
The purpose of the study was to examine the effects of personality, anxiety sensitivity, intolerance of uncertainty and self-esteem on different anxiety symptoms. A total of 436 university students completed measures of personality, anxiety sensitivity, intolerance of uncertainty, self-esteem, and symptoms of panic, worry and social anxiety. Results have shown that neuroticism, conscientiousness and psychological concerns (anxiety sensitivity) predict symptoms of panic and that psychological concerns mediate the relationship between neuroticism and panic. Worry was predicted by neuroticism, prospective and inhibitory intolerance of uncertainty and self-liking, with intolerance of uncertainty mediating between neuroticism and worry. Finally, neuroticism, openness to experiences and extraversion, as well as social concerns (anxiety sensitivity), inhibitory intolerance of uncertainty and self-liking predicted social anxiety. Social concerns, inhibitory intolerance of uncertainty and self-liking mediated the effects of neuroticism and extraversion on social anxiety. Results offer support to neuroticism being a universal risk factor and anxiety sensitivity, intolerance of uncertainty and self-esteem having specific effects on anxiety symptoms.